Connectivity between supplementary motor complex and primary motor cortex: a dual-coil paired-pulse TMS study - Kim, Hakjoo; Lei, Yuming; Bao, Shancheng; Huynh, Angelina T.; Buchanan, John J.; Bernard, Jessica A.; Brown, Joshua C.; Wright, David L. (Frontiers in Neurology, 2025)
Dual-coil paired-pulse transcranial magnetic stimulation (ppTMS) has garnered interest for its potential in elucidating neural circuit dynamics. In this study, the dual-coil ppTMS was utilized to assess the effective connectivity between the supplementary motor complex (SMC) and the primary motor cortex (M1) in humans. A robust facilitatory connection between the SMC and M1 was observed, manifested as a 19% increase in mean peak-to-peak motor-evoked potentials following conditioning of SMC 7 ms prior to M1 stimulation. Importantly, the facilitatory influence of SMC was found in subjects who received conditioning stimulation 4 cm anterior to Cz, but not in those stimulated at 5 cm, 6 cm, or 7 cm. While previous work has focused on demonstrating important temporal dynamics for SMC-M1 plasticity, the present findings highlight a critical contribution of spatial specificity for the modulation of SMC-M1 circuitry.